Investigation of route optimization for mobile ad hoc NEMO (MANEMO) based proposals - Mosa, Ahmed A.; Hassan Abdalla Hashim, Aisha; Saeed, Rashid Abdelhaleem; Khalifa, Othman Omran (INSI Publications, 2011)
In the doorway of the Mobile IPv6 (MIPv6), it was considered as the standard protocol that support the host mobility. Due to its limitation that does not support the Mobile Routers (MRs), the Internet Engineering Task Force (IETF) has introduced the NEMO Basic Support (NEMO BS) protocol. The Mobile Ad hoc Network (MANET) routing protocol provides the local and the direct communications between two mobile devices within the Nested NEMO (when multiple MRs are connected together). Integrating the MANET and the NEMO (MANEMO) provides the necessary additions to the existing protocols (IPv6, Neighbour Discovery (ND), and NEMO) to support the Nested MRs. It provides a mechanism to select the most suitable path to the Exit Router (ER) as a default in the MANEMO Fringe Stub (MFS). The NCM (NEMO centric MANEMO) protocol is introduced to address the Nested NEMO issues (e.g. pinball problem) by using the MANET routing a protocol (i.e. OLSR), while the MCM (MANET centric MANEMO) protocol is introduced to address the MANET problem (e.g. Internet connectivity). The main aim of this paper is to investigate the current approaches that are introduced to provide the Route Optimization (RO) for the NEMO. It highlights the strengths and the limitations of these approaches. Both the qualitative and the quantitative evolutions of these proposals are hereby presented.